Антология выдающихся достижений в науке и технике. Часть 45: традиционная энергетика. Гидравлические электрические станции: состояние и перспективы их развития - Баранов, Михаил Иванович (НТУ "ХПИ", 2018)
Приведен краткий научно-технический обзор о современном состоянии и перспективах развития мировой гидроэнер-гетики. Рассмотрены основные схемы построения и виды гидравлических электрических станций (ГЭС). Указаны преимущества и недостатки ГЭС перед другими видами электрических станций, генерирующих электричество. Приведены основные технические характеристики крупнейших ГЭС мира и Украины. Отмечена важная роль гидроэнергетики в объемах годовой выработки электроэнергии в ряде стран мира. Обозначены проблемные задачи в области гидроэнергетики мира и Украины.

Preparation of brief scientific and technical review about the state, achievements, problems and prospects of development of world hydraulic power engineering. Known scientific methods of collection, analysis and analytical treatment of the opened scientific and technical information, present in scientific monographs, journals and internet sources, high meaningfulness in area of hydraulic power engineering. A brief analytical scientific and technical review is resulted about the present state, achievements, problem tasks and prospects of development of hydraulic power engineering in the industrially developed countries of the world. Considerable progress is marked in development and creation of technical base of modern hydraulic power engineering including powerful hydraulic turbines and hydraulic electric generators. Existent classification of the hydraulic power plants (HPPs) is resulted. Basic types and constructions of powerful hydraulic turbines, in-use on modern HPPs are presented. Basic kinds and technical descriptions of powerful hydraulic electric generators used at modern HPPs are indicated. Information is resulted about the largest in the world ordinary HPPs and hydraulic heat-sink HPPs. Hydraulic power engineering of Ukraine is considered and descriptions of basic domestic HPPs are described. Advantages and failings of HPPs are marked in comparison with the thermal and nuclear power plants. Information is presented about absolute volumes of electric power produced by HPPs in a number of the industrial developed countries of the world. Quantitative indexes are resulted for today in the world of reserve of hydraulic power resources on the continents of our planet. A conclusion is done that this reserve of hydraulic power resources is mainly concentrated in the countries of Asia. It is indicated that hydraulic power engineering of the world produces presently up to 21 % of electric energy in annual world in the electrical energy balance. Some problem tasks of world hydraulic power engineering are indicated. Certain prospects are outlined in development of hydraulic power in the world and in Ukraine. Systematization is executed as short structured of scientific and technical review of the scientific and technical materials touching functioning of such important sector of world economy as hydraulic power engineering known from the open sources in informative space. Material is expounded from positions of scientist-electrophysics in an accessible for a wide reader new informatively-rich content form. Popularization and deepening for students, engineers and technical specialists and researchers of front-rank scientific and technical knowledge in area of modern hydraulic power engineering extending their scientific range of interests and promoting further development of scientific and technical progress in society.
An anthology of the distinguished achievements in science and technique. Part 45: Traditional power engineering. Hydraulic power plants: state and prospects of their development
Keywords: гидроэлектростанция; гидротурбины; гидроэнергетика; электрогидрогенераторы; hydropower engineering; hydraulic turbines; hydraulic electric generators